THE INFLUENCE OF CLOSE FRIENDS ON COLLABORATIVE LEARNING AT POLITEKNIK LP3I JAKARTA - Nurul Oktaviani; Muhamad Yusuf Segaff; Metya Lutviani (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Project-Based Learning (PjBL) at Politeknik LP3I Jakarta requires students to collaborate effectively in completing projects that simulate real workplace situations. However, students’ participation levels within collaborative groups remain inconsistent. This study aimed to examine the influence of close friend relationships on students' collaborative learning. A quantitative approach with a descriptive research design was employed involving 59 first- and second-year students selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire distributed via Google Forms and analyzed using IBM SPSS Statistics Version 25 through simple linear regression and the independent t-test. The findings indicate that close friend influence has a positive and statistically significant effect on collaborative learning, with a calculated t-value of 7.361 exceeding the critical t-value of 1.672 (p = 0.000). The resulting regression equation is Y = 13.788 + 0.771X, while the coefficient of determination (R² = 0.463) indicates that close friend influence explains 46.3% of the variance in collaborative learning. These findings suggest that social support and interpersonal closeness substantially enhance students' participation, communication, and teamwork effectiveness within project-based collaborative learning environments.